Cocktail of reactive species generated by cold atmospheric plasma: oral administration induces non-small cell lung cancer cell death. (22nd February 2021) - Song, Chang-Hyun; Attri, Pankaj; Ku, Sae-Kwang; Han, Ihn; Bogaerts, Annemie; Choi, Eun Ha
Abstract: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer, with 85% of all lung cancer reported as NSCLC. Moreover, there are no effective treatments in advanced NSCLC. This study shows for the first time that oral administration of plasma-treated water (PTW) can cure advanced NSCLC. The cold plasma in water generates a cocktail of reactive species, and oral administration of this cocktail to mice showed no toxicities even at the highest dose of PTW, after a single dose and repeated doses for 28 d in mice. In vivo studies reveal that PTW showed favorable anticancer effects on chemo-resistant lung cancer, similarly to gefitinib treatment as a reference drug in a chemo-resistant NSCLC model. The anticancer activities of PTW seem to be involved in inhibiting proliferation and angiogenesis and enhancing apoptosis in the cancer cells. Interestingly, the PTW contributes to enhanced immune response and improved cachexia in the model.